Pronomina Bahasa Melayu Dialek Melayu Kapuas Hulu Kecamatan Jongkong - Rini Agustina (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas PGRI Ronggolawe, 2024)
This research aims to describe Malay pronouns in the Kapuas Hulu Malay Dialect, Jongkong District. The method used in this research is a descriptive method and a form of qualitative research. The data source in this research is the community. The results of data analysis in this research obtained data in the form of Malay pronominal forms of the Kapuas Hulu Malay Dialect which include personal pronouns, demonstrative pronouns and question pronouns. The function of pronouns in the Malay Kapuas Hulu dialect functions as subject, predicate, object and adverb. The meaning of pronouns in the Kapuas Hulu Dialect Malay language which have grammatical meaning and lexical meaning.